Feeding behaviour in a ‘basal’ tortoise provides insights on the transitional feeding mode at the dawn of modern land turtle evolution - Natchev, Nikolay; Tzankov, Nikolay; Werneburg, Ingmar; Heiss, Egon (PeerJ PrePrints, 2015)
Almost all extant land turtles are highly associated with terrestrial habitats and the few tortoises with high affinity to aquatic environment are found within the genus Manouria. Manouria belongs to a clade which forms the sister taxon to all remaining tortoises and is suitable to be used as a model for studying evolutionary transitions from water to land within modern turtles. We analysed the feeding behaviour of M. emys and due to its phylogenetic position, we hypothesise that the species might have retained some ancestral characteristics associated to aquatic lifestyle. We tested whether M. emys is able to feed both in aquatic and terrestrial environments as mud turtles do. In fact, M. emys repetitively tried to reach submerged food items in water, but always failed to grasp them and no suction feeding mechanism was applied. When feeding on land, M. emys showed another peculiar behaviour; it grasped food items by its jaws – a behaviour typical for aquatic or semiaquatic turtles – and not by the tongue as in the typical feeding mode in all tortoises studied so far. In M. emys, the hyolingual complex remained retracted during all food uptake sequences, but the food transport was entirely lingual based. The kinematical profile significantly differed from those described for other tortoises and from those proposed from the general models on the function of the feeding systems in lower tetrapods. We conclude that the feeding behaviour of M. emys might reflect a remnant of the primordial condition expected in the aquatic ancestor of tortoises.
Keywords: food uptake; turtle; evolution; Tetrapoda; feeding kinematics; transition to land